2016
DOI: 10.1007/s10637-016-0345-8
|View full text |Cite
|
Sign up to set email alerts
|

The kinesin Eg5 inhibitor K858 induces apoptosis but also survivin-related chemoresistance in breast cancer cells

Abstract: Inhibitors of kinesin spindle protein Eg5 are characterized by pronounced antitumor activity. Our group has recently synthesized and screened a library of 1,3,4-thiadiazoline analogues with the pharmacophoric structure of K858, an Eg5 inhibitor. We herein report the effects of K858 on four different breast cancer cell lines: MCF7 (luminal A), BT474 (luminal B), SKBR3 (HER2 like) and MDA-MB231 (basal like). We demonstrated that K858 displayed anti-proliferative activity on every analyzed breast cancer cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…Consequently, two cell lines that responded differently to RAD001 were selected: One sensitive (BT474) and the other resistant (MCF7). Our group has previously demonstrated that the upregulation of survivin, a specific IAP component, contributes to establishing resistance to taxanes and kinesin inhibitors in breast cancer cells (11,12). Survivin is a downstream target of the PI3k/Akt/mTOR pathway that is involved in drug resistance (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, two cell lines that responded differently to RAD001 were selected: One sensitive (BT474) and the other resistant (MCF7). Our group has previously demonstrated that the upregulation of survivin, a specific IAP component, contributes to establishing resistance to taxanes and kinesin inhibitors in breast cancer cells (11,12). Survivin is a downstream target of the PI3k/Akt/mTOR pathway that is involved in drug resistance (18).…”
Section: Discussionmentioning
confidence: 99%
“…Our group previously demonstrated that the upregulation of one of these IAPs, survivin, is involved in the resistance of human breast cancer cells to taxanes and also to K858, an inhibitor of kinesins (11,12). Given that survivin and estrogens are involved in the PI3k/Akt/mTOR transduction pathway, it is possible to hypothesize that survivin may be involved in the establishment of RAD001 resistance in certain hormone-responsive breast cancers.…”
mentioning
confidence: 99%
“…This impaired proliferation and induced apoptosis in MCF-7 and MDA231 cells, and it induced angiogenesis in vitro and in vivo [26]. Another KIF11 inhibitor, K85, was shown to have anticancer activity in breast cancer, though it also contributed to chemoresistance [27]. Adding to this existing research, we showed that there was a clinical association between the expression of KIF11 and breast cancer.…”
Section: Discussionmentioning
confidence: 84%
“…Recently, it has been shown that rK858 induces apoptosis and reverses the malignant invasive phenotype in human glioblastoma cells [24] and also influences survivin-related chemoresistance in breast cancer cells [25]. While the anti-Eg5 and anti-tumour activities of rK858 have been characterised in cell-based assays and in vivo, the biochemical and structural basis for inhibiting Eg5 not only by rK858, but also for the other two thiadiazole containing derivatives (S)-ARRY-520 and (R)-Litronesib, are still unknown.…”
Section: Introductionmentioning
confidence: 99%